Crown Lengthening Surgery: An Overview. Issue 4 (December 2019) - Kalsi, Harpoonam Jeet; Bomfim, Deborah I.; Hussain, Zahra; Rodriguez, Jose M.; Darbar, Ulpee
The term 'crown lengthening surgery' refers to a variety of techniques which aim to expose a greater amount of tooth structure around a tooth or group of teeth. The decision to treat and which technique to use will depend upon: the underlying aetiology; a thorough history and examination; results of any supporting investigations and a clear understanding of the intended outcome of treatment. This paper aims to provide an overview of crown lengthening surgery and is illustrated with clinical cases.